Users’ continuance intention toward online travel platforms: A bibliometric and systematic review of key drivers, boundary conditions, and future directions - Lee, Dongmei; Wang, Shiyu; Liu, Tianyu (Edelweiss Applied Science and Technology, 2025)
The proliferation of online travel platforms has fundamentally transformed the tourism industry, making users’ continuance intention a critical metric for platform success. This literature review synthesizes existing research on the factors influencing users’ continuance adoption intentions toward online travel platforms (websites and mobile apps). Through a dual-method approach of bibliometric analysis using CiteSpace (2014-2024) and a systematic literature review, the study maps the intellectual structure and evolutionary trends of the field. The analysis identifies core influencing factors such as perceived value, user trust, and technology characteristics, and key boundary conditions, including individual differences and contextual factors. Despite significant scholarly attention, the review identifies critical gaps, particularly the lack of focus on hybrid platforms that integrate transactional and review-based functionalities. It highlights the under-explored roles of perceived interactivity, perceived hedonicity, and network externality in shaping continuance intentions within these complex ecosystems. The paper concludes by proposing a future research agenda that calls for investigating the dynamic interplay of dual functionalities, integrating network effects, and adopting advanced methodological approaches to advance the understanding of user retention in hybrid online travel platforms.